1991
DOI: 10.1128/jb.173.2.443-448.1991
|View full text |Cite
|
Sign up to set email alerts
|

Natural transfer of conjugative transposon Tn916 between gram-positive and gram-negative bacteria

Abstract: The conjugative streptococcal transposon Tn916 was found to transfer naturally between a variety of gram-positive and gram-negative eubacteria. Enterococcus faecalis hosting the transposon could serve as a donor for Alcaligenes eutrophus, Citrobacter freundii, and Escherichia coli at frequencies of 10(-6) to 10(-8). No transfer was observed with several phototrophic species. Mating of an E. coli strain carrying Tn916 yielded transconjugants with Bacillus subtilis, Clostridium acetobutylicum, Enterococcus faeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
1
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(74 citation statements)
references
References 42 publications
(34 reference statements)
4
67
1
2
Order By: Relevance
“…This suggests that the transfer of tet(M) happened recently at this site. Tet(M) is frequently associated with a mobile element such as Tn916 which mediates its transfer between different bacterial species 9,31) including both Grampositive and Gram-negative bacteria 5) , phylogenetic analysis suggests that RPPs including tet(M) have an ancient origin 19) , and it is unlikely that each tet(M) evolved respectively in each host without mutations. Chee-Sanford et al 8) also suggested that the fact that several species of Enterococcus possessed the same allele of tet(M) indicated the likelihood of the transfer of tet(M) among species.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the transfer of tet(M) happened recently at this site. Tet(M) is frequently associated with a mobile element such as Tn916 which mediates its transfer between different bacterial species 9,31) including both Grampositive and Gram-negative bacteria 5) , phylogenetic analysis suggests that RPPs including tet(M) have an ancient origin 19) , and it is unlikely that each tet(M) evolved respectively in each host without mutations. Chee-Sanford et al 8) also suggested that the fact that several species of Enterococcus possessed the same allele of tet(M) indicated the likelihood of the transfer of tet(M) among species.…”
Section: Discussionmentioning
confidence: 99%
“…Clewell and Flannagan, 1993). Recently it was shown that not only can they be maintained in Gram-negative bacteria under selective pressure, but they can even transfer conjugatively from those to other Gramnegative or Gram-positive bacteria (Bertram et al, 1991). Transfer between Gram-positive bacteria is in general by a conjugative mechanism, during which the element is transferred as a circular intermediate.…”
Section: Open Questionsmentioning
confidence: 99%
“…To determine whether restriction barriers might be limiting the ability of DNA derived from E. coli to (2,16,19,23). In addition, there have been previous reports of gram-positive plasmids replicating in gram-negative bacteria (1,9,12,20 These results represent a significant step forward for studying the molecular biology of C. xyli subsp.…”
mentioning
confidence: 99%
“…cynodontis, and we have defined optimal conditions for transforming C. xyli subsp. cynodon-(is, which yielded more than 2 ,ug/ml; kanamycin, 67 ,ug/ml; neomycin, 25 p,g/ml; and gentamicin, 25 ,g/ml.…”
mentioning
confidence: 99%